Agama & Media Massa Tradisional dan Industrial - Nurdien Harry Kistanto (Endogami: Jurnal Ilmiah Kajian Antropologi, 2017)
It is increasingly clear that to understand religion in the 21st Century we must also understand media and the ways that religions are being remade through their interaction with modern media. Culture… is that complex whole which includes knowledge, beliefs, arts, morals, law, customs, and any other capabilities and habits acquired by man as a member of society. Mass media means technology that is intended to reach a mass audience. It is the primary means of communication used to reach the vast majority of the general public…. mass media of communication: the techniques and institutions through which centralized providers broadcast or distribute information and other forms of symbolic communication to large, heterogeneous and geographically dispersed audiences